MORPHOMETRIC STUDY OF TENDON EXTRAVALVING HORDEN VENTRICLE OF THE HEART WITH COMBINED MITRAL VALVE’ VICE - Stepanchuk, A. P. (World of Medicine and Biology, 2012)
Investigated drugs 8 hearts of people who died from acquired concomitant mitral valve defect against rheumatism. Extravalving tendon chord known in the literature as "false" and "additional" chords in the combined mitral valve have a similar arrangement, as in the ventricles of the heart without pathology. Extravalving tendinous chords are in the process of compensatory adjustment of the ventricles of the heart, with the subject of hypertrophy and strain, and it is thicker and shorter. The number and mix varies in each ventricle. Extravalving fibrosis anulyarnye chords are long (1,64 ± 0,05 sm) in the left ventricle than in the right ventricle (1,64 ± 0,05 sm). Extravalving thickness tendon chords ranges from 0.05 sm to 0.12 sm in both ventricles of the heart.